2002
DOI: 10.1021/cm010412m
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Mesoporous Silica Films with Fully Aligned Large Mesochannels Using Nonionic Surfactants

Abstract: Mesoporous silica films with uniaxially aligned large-sized mesochannels were prepared using nonionic alkyl poly(ethylene oxide) surfactants and a rubbing-treated polyimide coating. Although the increment of the pore size was small as long as conventional alkylammonium surfactants were used, the use of nonionic surfactants with poly(ethylene oxide) headgroups led to successful enlargement of the mesochannels. The directional distribution of the mesochannels in the films, which is estimated by in-plane X-ray di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
122
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 105 publications
(133 citation statements)
references
References 90 publications
10
122
1
Order By: Relevance
“…One of the most successful techniques to date for aligning mesochannels on a global scale (centimetre) has originated from a technique known as 'rubbing', pioneered by researchers at Cannon and Waseda University, and initially demonstrated for mesoporous particles in 1999 and for films in 2000 [5,[75][76][77][78][79][80]. The technique entails using a 10 nm thin polyimide coating to induce preferred unidirectional alignment and orientation of the mesochannels in the overlaying film.…”
Section: Chemical Epitaxymentioning
confidence: 99%
“…One of the most successful techniques to date for aligning mesochannels on a global scale (centimetre) has originated from a technique known as 'rubbing', pioneered by researchers at Cannon and Waseda University, and initially demonstrated for mesoporous particles in 1999 and for films in 2000 [5,[75][76][77][78][79][80]. The technique entails using a 10 nm thin polyimide coating to induce preferred unidirectional alignment and orientation of the mesochannels in the overlaying film.…”
Section: Chemical Epitaxymentioning
confidence: 99%
“…It is confirmed that the mesochannels in the MPS films are aligned perpendicularly to the rubbing direction (º = 0°). FWHM values of the peaks in the rocking curves are 11.3°for C 10 EO 10 and 7.8°for C 12 EO 10 . These values are larger than the value for C 16 EO 10 (2.8°), indicating that the degrees of the mesochannel alignment for C 10 EO 10 and C 12 EO 10 are lower than that for C 16 EO 10 .…”
Section: ¹1mentioning
confidence: 93%
“…This implies that the alkyl chains of the surfactants are slightly folded in the mesochannels. Figure 2 summarizes the in-plane XRD study of the MPS films synthesized using C 10 EO 10 and C 12 EO 10 . Figure 2a shows the º2ª» scanning profiles of the MPS films.…”
Section: ¹1mentioning
confidence: 99%
“…This alignment is passed on to the micellar structure of the surfactant molecules and can lead to a macroscopic alignment of the mesopores. The exact formation mechanism that leads to the alignment seems to depend on the matching of the chain length of the hydrophobic part of the surfactant to the chemical structure of the polyimide underlayer [44,45]. Zhao et al [41] and Naik et al [42] demonstrated that the shear flow exerted on films during dip coating can also influence mesopore alignment to some degree, but the correlation length of the obtained mesostructure might be low in these cases.…”
Section: Thin Film Deposition and Functionalization Techniquesmentioning
confidence: 99%